Aplicação de indicadores sociais para concessão de bolsas socioeconômicas na UFABC - Umbelino, Caroline de Souza (2018)
The student assistantship has provided lodging and boarding programs to students since 1930. The selection criteria are based upon socioeconomic analysis and profile classifications, which are based upon social indicators punctuation. Nevertheless, the profile analysis does not take the racial question into consideration as a problem of structural poverty, which reinforces the racial democracy discourse. In this regard, this thesis seeks to take into consideration edictal and resolution analysis, scholarship grant methods, and federal university grants through comparison among the most utilized criteria